Sensory characterisation of several red cultivar (Vitis vinifera L.) wines, using berry sugar accumulation as a physiological indicator and sequential harvest - Nell, Marissa (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.